Preparation method of aerogel composite material
Through sol spraying and fiber orientation arrangement technology, combined with natural gelation, solvent replacement, aging treatment and hydrophobic modification, the problems of complex and unstable performance of existing aerogel composite materials are solved, and efficient and simplified preparation technology and excellent material performance are achieved.
Patent Information
- Application Number
- CN202510084959.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing aerogel composite materials are made in complex methods, have high operating requirements, high energy consumption, and it is difficult to ensure consistency and stability in large-scale production. The materials have problems of aging and performance degradation during long-term use.
Using sol spraying and fiber orientation arrangement technology, uniform aerogel sol is sprayed on the directionally laid glass fiber skeleton through a high-pressure spray device to form a directionally arranged composite material structure. Then natural gelation, solvent replacement, aging treatment, hydrophobicity and durability modification were performed, and the aerogel composite material was finally obtained by multi-temperature gradient drying.
It realizes efficient composite of aerogel and fiber, improves the overall performance of the composite material, has higher strength, better thermal stability, significant hydrophobicity and durability, simplifies the process flow and reduces production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a method for preparing an aerogel composite material. Background Art
[0002] Aerogel composites achieve complementary and enhanced performance by combining aerogel with other high-performance materials. Their unique ultra-low density, high porosity, and excellent thermal insulation and adsorption properties have shown a wide range of application value in existing technologies. In the aerospace field, they are used as efficient thermal insulation materials to effectively protect aircraft from extreme temperature differences. In terms of environmental protection, their strong adsorption capacity helps purify the air and water. In the field of energy storage, aerogel composites are used as high-performance electrode materials to promote the development of new energy technologies.
[0003] The invention with authorization announcement number CN108911693B in the prior art is named as follows: A method for preparing an aerogel composite material, including molding tooling design, fiber matrix mold closing, impregnation molding, aging, solvent replacement and drying, wherein the impregnation molding is to sequentially use vacuum injection and pressure injection to impregnate the sol into the fiber matrix until a sol-gel reaction occurs. The present invention also proposes an aerogel composite material with large thickness and adjustable thickness, no stratification and cracks in internal quality, and good density uniformity, which is obtained by the above-mentioned preparation method. The preparation method of the present invention significantly improves the thermal insulation performance of the thick aerogel composite material, which can be used for internal and external thermal insulation in the aerospace field when operating in a high-temperature environment for a long time. In addition, the method can prepare special-shaped components with different profile specifications, which has guiding significance for the integrated molding of internal and external heat protection of various aircraft; However, the preparation process of this application is relatively complicated and requires high skills from the operators. The slightest carelessness may affect the final quality of the product. Secondly, some preparation steps such as supercritical drying consume a lot of energy, which increases production costs and is not conducive to the market promotion of the product. Furthermore, for large-scale production, how to ensure the performance consistency and stability of each batch of products is still a problem that needs to be solved. Finally, the performance of the material will change during long-term use, such as whether aging, performance degradation and other problems will occur. Summary of the invention
[0004] The invention provides a method for preparing an aerogel composite material, which solves the problems of poor thermal stability and uneven sol in the related art.
[0005] The technical solution of the present invention is as follows: A method for preparing an aerogel composite material comprises the following steps: Step S1: fiber pretreatment, cleaning the glass fiber to remove surface impurities, washing with deionized water, and drying in an oven to constant weight; Step S2: selecting methyltrimethoxysilane as a silicon source, mixing the silicon source compound with an ethanol solvent according to a mass ratio, and using an ethanol sedimentation desalination method to obtain a uniform sol; Step S3: using an automated fiber laying device to lay the pretreated fibers in a mold in a specific direction, and using a spray device to evenly spray the aerogel sol on the fiber skeleton to form a directional composite material structure; Step S4: leaving the fiber skeleton sprayed with the sol to stand for natural gelation, and gentle heating can be used to accelerate the gelation process; Step S5: using a mixture of water and anhydrous ethanol to replace the gel solvent, and then performing an aging treatment at a suitable temperature to stabilize the gel structure; Step S6: soaking the composite material with a mixture of a hydrophobic reagent and an organic solvent to enhance its hydrophobicity and durability, and then performing secondary modification with a cross-linking agent; Step S7: drying the modified composite material under biomimetic normal pressure, using sodium bicarbonate solution as a solvent for drying, using the carbon dioxide generated in the reaction to in-situ support the pore structure to prevent the pore structure from collapsing, and performing molding processing to obtain the final aerogel composite material product.
[0006] As a preferred embodiment of the present invention, in step S1, the fiber pretreatment, cleaning the glass fiber, removing surface impurities, washing with deionized water, and drying in an oven to constant weight are as follows: (1) Immerse the glass fiber completely in deionized water and use ultrasonic cleaning equipment to clean it at a frequency of 30-50kHz for 20-30 minutes to ensure that surface impurities and oil stains are completely removed; (2) After cleaning, use absorbent paper to absorb excess water from the surface of the glass fiber, and then place it in an oven set at 80-100°C to dry for 3-4 hours until it reaches a constant weight.
[0007] As a preferred embodiment of the present invention, in step S2, methyltrimethoxysilane is selected as the silicon source, the silicon source compound is mixed with the ethanol solvent according to a mass ratio, and the specific steps of obtaining a uniform sol by an ethanol sedimentation desalination method are as follows: (1) Mix the silicon source compound and the ethanol solvent in a mass ratio of 1:5-1:10, and stir them at 300-500 rpm for 30 minutes using a magnetic stirrer at room temperature to ensure uniform mixing; (2) Add salt and stir the mixture to allow ethanol to fully contact with the salt and silicon source compound, accelerate the dissolution and precipitation of the salt, and let the mixture stand for a period of time to allow the ethanol and salt to fully react and other impurities to settle. The salt will gradually dissolve in the ethanol, and other impurities will form solid precipitation; (3) Using a filter or a centrifuge to separate the ethanol gel solution containing the dissolved salt from other impurities that have settled down, until a transparent and uniform sol is formed.
[0008] As a preferred embodiment of the present invention, in step S3, the pretreated fibers are laid in a mold in a specific direction using an automated fiber laying device, and the aerogel sol is evenly sprayed on the fiber skeleton using a spray device to form a directional composite material structure. The specific steps are as follows: (1) Using automated fiber laying equipment, the pretreated glass fibers are laid in a mold in preset directions of 0°, 45°, and 90° to form a multi-layer directional fiber skeleton; (2) Use a high-pressure spray device to evenly spray the sol onto the fiber skeleton at a pressure of 0.5-1.0 MPa to ensure that the sol fully penetrates and wraps each layer of fiber to form a dense composite material structure.
[0009] As a preferred embodiment of the present invention, in step S4, the fiber skeleton sprayed with the sol is allowed to stand for natural gelation, and gentle heating may be used to accelerate the gelation process. The specific steps are as follows: (1) The fiber skeleton sprayed with the sol is left to stand at room temperature for 12-24 hours to allow for a natural gelation process; (2) The composite material can be placed in an oven set at 30-50°C for 2-6 hours to accelerate gelation.
[0010] As a preferred embodiment of the present invention, in step S5, the gel is subjected to solvent replacement using a mixture of water and anhydrous ethanol, and then subjected to aging treatment at a suitable temperature to stabilize the gel structure. The specific steps are as follows: (1) using a mixture of water and anhydrous ethanol in a volume ratio of 1:2-1:5 to perform multiple solvent replacements on the gel, and using a centrifuge or vacuum filtration device to remove residual solvent after each replacement until most of the ethanol is replaced; (2) The replaced composite material is placed in an oven set at a temperature of 60-80°C for aging for 24-48 hours to further stabilize the gel structure.
[0011] As a preferred embodiment of the present invention, in step S6, the composite material is soaked with a mixture of a hydrophobic agent and an organic solvent to enhance its hydrophobicity and durability, and then the composite material is subjected to secondary modification with a cross-linking agent. The specific steps are as follows: (1) The composite material is completely immersed in a solution of polydimethylsiloxane and n-hexane in a volume ratio of 1:15 to 1:10 for 6-12 hours to enhance the hydrophobicity of the material; (2) After the immersion is completed, the composite material is taken out and rinsed with n-hexane, and then immersed in a cross-linking agent solution containing glutaraldehyde with a concentration of 0.5%-1.0%. The glutaraldehyde concentration is soaked at room temperature for 1-2 hours for secondary modification to enhance the durability of the material.
[0012] As a preferred embodiment of the present invention, in step S7, the modified composite material is dried at bionic atmospheric pressure, dried using a sodium bicarbonate solution solvent, the carbon dioxide generated in the reaction is used to in-situ support the pore structure to prevent the pore structure from collapsing, and the molding process is performed to obtain the final aerogel composite material product. The specific steps are as follows: (1) Sodium bicarbonate solution is evenly coated on the surface of the composite material, and then the composite material is placed in a multi-temperature gradient oven for drying. First, it is dried at 40-60°C for 4-6 hours, then gradually heated to 80-100°C for 6-8 hours, and finally dried at 100-120°C for 2-4 hours. Drawing on the dragonfly eclosion process, the sodium bicarbonate solution generates carbon dioxide gas during the heating process. The gas forms tiny bubbles inside the gel, thereby supporting the pore structure of the gel, making it completely dry and making the pore structure stronger. (2) After drying, cutting, grinding and other molding processes are carried out according to product requirements to finally obtain an aerogel composite material product of the required shape and size.
[0013] The working principle and beneficial effects of the present invention are: 1. The present invention uses sol spraying and fiber directional arrangement technology to accurately spray the uniformly prepared aerogel sol onto a glass fiber skeleton laid in a specified direction through a high-pressure spray device. In this process, the sol can fully penetrate and evenly wrap each layer of fiber to form a three-dimensional network structure with good mechanical properties and thermal insulation properties, which not only achieves efficient composite of aerogel and fiber, but also improves the overall performance of the composite material, so that the product has higher strength and better thermal stability.
[0014] 2. The present invention combines multi-temperature gradient drying and bionic normal pressure drying technology to perform a drying treatment on the modified aerogel composite material under fine control. By gradually increasing the temperature at different temperature stages, the cracking or deformation of the material caused by uneven temperature stress during the drying process is effectively avoided, thereby ensuring the drying quality of the composite material, shortening the drying cycle, and improving production efficiency. In addition, drawing on the dragonfly eclosion process, the sodium bicarbonate solution is heated to generate carbon dioxide gas, and the gas forms tiny bubbles inside the gel, thereby supporting the pore structure of the gel and making the gel stronger. The multi-temperature gradient treatment also promotes further optimization of the internal structure of the material, enhances the durability and service life of the composite material, avoids the high pressure and high temperature conditions required for the traditional supercritical drying method, and thus simplifies the process flow.
[0015] 3. The present invention uses methyltrimethoxysilane as the silicon source. The silicon source can reduce the number of hydroxyl groups during hydrolysis, avoiding the generation of a large number of silicon-oxygen bonds. At the same time, the hydrophobic silicon methyl groups repel each other due to the steric effect, which can make the silica aerogel obtain a coarsened structure, thereby giving it a certain flexibility. A uniform sol is obtained by the ethanol sedimentation desalination method, avoiding the complicated and high-cost ion exchange resin sodium removal, and avoiding the environmental pressure caused by a large amount of wastewater.
[0016] The present invention adopts double surface modification technology, firstly uses a hydrophobic agent mixed with an organic solvent to soak the composite material to enhance its hydrophobic properties, and then uses a cross-linking agent for secondary modification to improve the durability and stability of the material. This modification method effectively improves the waterproof and moisture-proof ability of the aerogel composite material, and also enhances the adaptability of the material in harsh environments. The composite material after double modification has excellent comprehensive performance, higher weather resistance, better chemical corrosion resistance and longer service life, which provides a guarantee for the application of the material in outdoor, humid or chemical environments.
[0017] In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail as follows. DETAILED DESCRIPTION Example
[0018] This embodiment proposes a method for preparing an aerogel composite material, comprising step S1: fiber pretreatment, cleaning the glass fiber to remove surface impurities, cleaning with deionized water, placing the glass fiber in an oven to dry to constant weight after cleaning, completely immersing the glass fiber in deionized water, and using an ultrasonic cleaning device to clean it at a frequency of 30kHz for 20 minutes to ensure that surface impurities and oil stains are completely removed; after cleaning, using absorbent paper to absorb excess water from the surface of the glass fiber, and then placing it in an oven set at a temperature of 80°C to dry, and maintaining it for 3 hours until a constant weight state is reached; Step S2: Methyltrimethoxysilane is selected as a silicon source, and the silicon source compound and the ethanol solvent are mixed according to a mass ratio, and an ethanol sedimentation desalination method is used to obtain a uniform sol, and the silicon source compound and the ethanol solvent are mixed according to a mass ratio of 1:5, and a magnetic stirrer is used to stir at a speed of 300 rpm for 30 minutes at room temperature to ensure uniform mixing; salt is added to stir the mixture to allow ethanol to fully contact with the salt and the silicon source compound to accelerate the dissolution and sedimentation of the salt, and the mixture is allowed to stand for a period of time to allow ethanol and salt to fully react and other impurities to settle down, and the salt gradually dissolves in the ethanol, and other impurities will form solid precipitation; a filter or a centrifuge is used to separate the ethanol gel solution in which the salt is dissolved from other impurities that have settled down by filtering or centrifuging until a transparent and uniform sol is formed; Step S3: using an automated fiber laying device, laying the pretreated fibers in a mold in a specific direction, and using a spray device to evenly spray the aerogel sol on the fiber skeleton to form a directional composite material structure; using an automated fiber laying device, laying the pretreated glass fibers in the mold in preset directions of 0°, 45°, and 90° to form a multi-layer directional fiber skeleton; using a high-pressure spray device, evenly spraying the sol on the fiber skeleton at a pressure of 0.5 MPa to ensure that the sol fully penetrates and wraps each layer of fiber to form a dense composite material structure; Step S4: The fiber skeleton sprayed with the sol is allowed to stand for natural gelation. Mild heating can be used to accelerate the gelation process. The fiber skeleton sprayed with the sol is allowed to stand for 12 hours at room temperature for natural gelation. The composite material can be placed in an oven set at 30°C and heated for 2 hours to accelerate gelation. Step S5: using a mixture of water and anhydrous ethanol to perform solvent replacement on the gel, and then performing an aging treatment at a suitable temperature to stabilize the gel structure, using a mixture of water and anhydrous ethanol in a volume ratio of 1:2 to perform solvent replacement on the gel multiple times, and using a centrifuge or a vacuum filtration device to remove the residual solvent after each replacement until most of the ethanol is replaced; placing the replaced composite material in an oven set at a temperature of 60°C for aging treatment for 24 hours to further stabilize the gel structure; Step S6: soaking the composite material with a mixture of a hydrophobic reagent and an organic solvent to enhance its hydrophobicity and durability, and then performing secondary modification with a cross-linking agent, completely immersing the composite material in a solution of polydimethylsiloxane and n-hexane in a volume ratio of 1:15 for 6 hours to enhance the hydrophobicity of the material; after the immersion, taking out the composite material and rinsing it with n-hexane, and then immersing it in a cross-linking agent solution containing glutaraldehyde with a glutaraldehyde concentration of 0.5%, and soaking it at room temperature for 1 hour for secondary modification to enhance the durability of the material; Step S7: subjecting the modified composite material to bionic atmospheric drying, using sodium bicarbonate solution as a solvent for drying, using the carbon dioxide generated in the reaction to in-situ support the pore structure to prevent the pore structure from collapsing, and performing molding processing, uniformly coating the surface of the composite material with sodium bicarbonate solution, and then placing the composite material in a multi-temperature gradient oven for drying, first drying at 40°C for 4 hours, then gradually heating to 80°C for drying for 6 hours, and finally drying at 100°C for 2 hours. Drawing on the dragonfly eclosion process, the sodium bicarbonate solution generates carbon dioxide gas during the heating process, and the gas forms tiny bubbles inside the gel, thereby supporting the pore structure of the gel, making it thoroughly dry and making the pore structure more solid; after drying, cutting, grinding and other molding processes are performed according to product requirements to finally obtain an aerogel composite material product of the required shape and size. Example
[0019] Based on the same concept as the above-mentioned embodiment 1, this embodiment also proposes a method for preparing an aerogel composite material, including step S1: fiber pretreatment, cleaning the glass fiber to remove surface impurities, cleaning with deionized water, placing it in an oven to dry to constant weight after cleaning, completely immersing the glass fiber in deionized water, using an ultrasonic cleaning device to clean it at a frequency of 40kHz for 30 minutes to ensure that surface impurities and oil stains are completely removed; after cleaning, using absorbent paper to absorb excess water on the surface of the glass fiber, and then placing it in an oven set at a temperature of 90°C to dry, and maintaining it for 4 hours until a constant weight state is reached; Step S2: Methyltrimethoxysilane is selected as a silicon source, and the silicon source compound and the ethanol solvent are mixed according to a mass ratio, and an ethanol sedimentation desalination method is used to obtain a uniform sol, and the silicon source compound and the ethanol solvent are mixed according to a mass ratio of 1:7, and a magnetic stirrer is used to stir at a speed of 400 rpm for 30 minutes at room temperature to ensure uniform mixing; salt is added to stir the mixture to allow ethanol to fully contact with the salt and the silicon source compound to accelerate the dissolution and sedimentation of the salt, and the mixture is allowed to stand for a period of time to allow ethanol and salt to fully react and other impurities to settle down, and the salt gradually dissolves in the ethanol, and other impurities will form solid precipitation; a filter or a centrifuge is used to separate the ethanol gel solution in which the salt is dissolved from other impurities that have settled down by filtering or centrifuging until a transparent and uniform sol is formed; Step S3: using an automated fiber laying device, laying the pretreated fibers in a mold in a specific direction, and using a spray device to evenly spray the aerogel sol on the fiber skeleton to form a directional composite material structure; using an automated fiber laying device, laying the pretreated glass fibers in the mold in preset directions of 0°, 45°, and 90° to form a multi-layer directional fiber skeleton; using a high-pressure spray device, evenly spraying the sol on the fiber skeleton at a pressure of 0.7 MPa to ensure that the sol fully penetrates and wraps each layer of fiber to form a dense composite material structure; Step S4: The fiber skeleton sprayed with the sol is allowed to stand for natural gelation. Mild heating can be used to accelerate the gelation process. The fiber skeleton sprayed with the sol is allowed to stand at room temperature for 18 hours to perform a natural gelation process. The composite material can be placed in an oven set at 40°C and heated for 3 hours to accelerate the gelation. Step S5: using a mixture of water and anhydrous ethanol to perform solvent replacement on the gel, and then performing an aging treatment at a suitable temperature to stabilize the gel structure, using a mixture of water and anhydrous ethanol in a volume ratio of 1:3 to perform multiple solvent replacements on the gel, and using a centrifuge or a vacuum filtration device to remove the residual solvent after each replacement until most of the ethanol is replaced; placing the replaced composite material in an oven set at 80°C for aging treatment for 36 hours to further stabilize the gel structure; Step S6: soaking the composite material with a mixture of a hydrophobic reagent and an organic solvent to enhance its hydrophobicity and durability, and then performing secondary modification with a cross-linking agent, completely immersing the composite material in a solution of polydimethylsiloxane and n-hexane in a volume ratio of 1:12 for 10 hours to enhance the hydrophobicity of the material; after the immersion, taking out the composite material and rinsing it with n-hexane, and then immersing it in a cross-linking agent solution containing glutaraldehyde with a glutaraldehyde concentration of 0.8%, and soaking it at room temperature for 2 hours for secondary modification to enhance the durability of the material; Step S7: subjecting the modified composite material to bionic normal pressure drying, using sodium bicarbonate solution as a solvent for drying, using the carbon dioxide generated in the reaction to in-situ support the pore structure to prevent the pore structure from collapsing, and performing molding processing, uniformly coating the surface of the composite material with sodium bicarbonate solution, and then placing the composite material in a multi-temperature gradient oven for drying, first drying at 50°C for 5 hours, then gradually heating to 90°C for drying for 7 hours, and finally drying at 110°C for 3 hours. Drawing on the dragonfly eclosion process, the sodium bicarbonate solution generates carbon dioxide gas during the heating process, and the gas forms tiny bubbles inside the gel, thereby supporting the pore structure of the gel, making it thoroughly dry and making the pore structure more solid; after drying, cutting, grinding and other molding processes are performed according to product requirements to finally obtain an aerogel composite material product of the required shape and size. Example
[0020] Based on the same concept as the above-mentioned embodiment 1, this embodiment proposes a method for preparing an aerogel composite material, including step S1: fiber pretreatment, cleaning the glass fiber to remove surface impurities, cleaning with deionized water, placing it in an oven to dry to constant weight after cleaning, completely immersing the glass fiber in deionized water, using an ultrasonic cleaning device to clean it at a frequency of 50kHz for 30 minutes to ensure that surface impurities and oil stains are completely removed; after cleaning, using absorbent paper to absorb excess water on the surface of the glass fiber, and then placing it in an oven set at a temperature of 100°C to dry, and maintaining it for 4 hours until a constant weight state is reached; Step S2: Methyltrimethoxysilane is selected as a silicon source, and the silicon source compound and the ethanol solvent are mixed according to a mass ratio, and an ethanol sedimentation desalination method is used to obtain a uniform sol, and the silicon source compound and the ethanol solvent are mixed according to a mass ratio of 1:10, and a magnetic stirrer is used to stir at a speed of 500 rpm for 30 minutes at room temperature to ensure uniform mixing; salt is added to stir the mixture to allow ethanol to fully contact with the salt and the silicon source compound to accelerate the dissolution and sedimentation of the salt, and the mixture is allowed to stand for a period of time to allow ethanol and salt to fully react and other impurities to settle down, and the salt gradually dissolves in the ethanol, and other impurities will form solid precipitation; a filter or a centrifuge is used to separate the ethanol gel solution in which the salt is dissolved from other impurities that have settled down by filtering or centrifuging until a transparent and uniform sol is formed; Step S3: using an automated fiber laying device, laying the pretreated fibers in a mold in a specific direction, and using a spray device to evenly spray the aerogel sol on the fiber skeleton to form a directional composite material structure; using an automated fiber laying device, laying the pretreated glass fibers in the mold in preset directions of 0°, 45°, and 90° to form a multi-layer directional fiber skeleton; using a high-pressure spray device, evenly spraying the sol on the fiber skeleton at a pressure of 1.0 MPa to ensure that the sol fully penetrates and wraps each layer of fiber to form a dense composite material structure; Step S4: The fiber skeleton sprayed with the sol is allowed to stand for natural gelation. Mild heating can be used to accelerate the gelation process. The fiber skeleton sprayed with the sol is allowed to stand for 24 hours at room temperature for natural gelation. The composite material can be placed in an oven set at 50°C and heated for 6 hours to accelerate gelation. Step S5: using a mixture of water and anhydrous ethanol to perform solvent replacement on the gel, and then performing an aging treatment at a suitable temperature to stabilize the gel structure, using a mixture of water and anhydrous ethanol in a volume ratio of 1:5 to perform solvent replacement on the gel multiple times, and using a centrifuge or a vacuum filtration device to remove the residual solvent after each replacement until most of the ethanol is replaced; placing the replaced composite material in an oven set at 80°C for aging treatment for 48 hours to further stabilize the gel structure; Step S6: soaking the composite material with a mixture of a hydrophobic reagent and an organic solvent to enhance its hydrophobicity and durability, and then performing secondary modification with a cross-linking agent, completely immersing the composite material in a solution of polydimethylsiloxane and n-hexane in a volume ratio of 1:10 for 12 hours to enhance the hydrophobicity of the material; after the immersion, taking out the composite material and rinsing it with n-hexane, and then immersing it in a cross-linking agent solution containing glutaraldehyde with a glutaraldehyde concentration of 1.0%, and soaking it at room temperature for 2 hours for secondary modification to enhance the durability of the material; Step S7: drying the modified composite material under bionic normal pressure, using sodium bicarbonate solution as a solvent for drying, using the carbon dioxide generated in the reaction to support the pore structure in situ to prevent the pore structure from collapsing, and performing molding processing, uniformly coating the surface of the composite material with sodium bicarbonate solution, and then placing the composite material in a multi-temperature gradient oven for drying, first drying at 60°C for 6 hours, then gradually heating to 100°C for drying for 8 hours, and finally drying at 120°C for 4 hours. Drawing on the dragonfly eclosion process, the sodium bicarbonate solution generates carbon dioxide gas during the heating process, and the gas forms tiny bubbles inside the gel, thereby supporting the pore structure of the gel, making it thoroughly dry and making the pore structure more solid; after drying, cutting, grinding and other molding processes are performed according to product requirements to finally obtain an aerogel composite material product of the required shape and size.
[0021] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the spraying conditions, sol viscosity and spraying pressure are adjusted to simulate the situation of insufficient sol penetration, and the natural gelation time is shortened to 6 hours. At the same time, the accelerated gelation oven step is omitted, and all other steps and conditions remain unchanged. The purpose of Comparative Example 1 is to deeply explore the specific effects of these changes on the sol permeability, gelation process integrity and internal structure and durability of the aerogel composite material.
[0022] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that by extending the aging treatment time to 60 hours, the enhancing effect of longer aging on the structural stability and durability of the aerogel composite material is evaluated, and at the same time, the ratio of polydimethylsiloxane to n-hexane is adjusted or other methods are used to enhance the hydrophobicity of the material, so as to explore the additional contribution of hydrophobic treatment to the durability of the material. The purpose is to clarify the key role of aging treatment time and hydrophobicity in improving the service life of the material and provide data support for material optimization strategies.
[0023] The aerogel composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested to show the performance of these materials in different key test indicators, including mechanical strength, thermal stability, hydrophobic angle, and durability cycle times, and with reference to ISO 18502:2017 Aerogel Material Performance Test Standard. The experimental data are shown in Table 1: Table 1
[0024] As can be seen from Table 1, the aerogel composite material prepared by the sol-gel composite preparation method adopted in this application has good mechanical strength, thermal stability, hydrophobicity and durability; Compared with Example 1, Example 1 uses a multi-layer oriented fiber skeleton and an optimized sol spraying process, while Comparative Example 1 is insufficient in sol penetration, resulting in that the mechanical strength and durability of the obtained composite material are significantly lower than those of Example 1; Compared with Example 1 and Comparative Example 2, Example 1 uses a specific ratio of silicon source compound and ethanol solvent to mix and perform drying treatment under multiple temperature gradients, while Comparative Example 2 prolongs the aging time, but fails to perform comprehensive optimization in sol preparation and drying process like Example 1. It can be seen from the table that Example 1 is not only superior to Comparative Example 2 in mechanical strength and thermal stability, but also performs well in hydrophobicity and durability; Summary: The example prepared an aerogel composite material with excellent mechanical strength, high thermal stability, significant hydrophobicity and durability through sol preparation, multi-layer oriented fiber skeleton laying, high-pressure sol spraying, multi-temperature gradient drying, and hydrophobicity and durability enhancement treatment. The mechanical strength and durability of comparative example 1 decreased due to insufficient sol penetration, and the performance improvement of comparative example 2 was limited due to the failure to comprehensively optimize the sol preparation and drying processes. Therefore, these comparative results prove the effectiveness and practicality of the preparation method adopted in Example 1.
[0025] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing an aerogel composite material, characterized in that: The following steps are involved: Step S1: fiber pretreatment, cleaning the glass fiber to remove surface impurities, washing with deionized water, and drying in an oven to constant weight; Step S2: selecting methyltrimethoxysilane as a silicon source, mixing the silicon source compound with an ethanol solvent according to a mass ratio, and using an ethanol sedimentation desalination method to obtain a uniform sol; Step S3: using an automated fiber laying device to lay the pretreated fibers in a mold in a specific direction, and using a spray device to evenly spray the aerogel sol on the fiber skeleton to form a directional composite material structure; Step S4: leaving the fiber skeleton sprayed with the sol to stand for natural gelation, and gentle heating can be used to accelerate the gelation process; Step S5: using a mixture of water and anhydrous ethanol to replace the gel solvent, and then performing an aging treatment at a suitable temperature to stabilize the gel structure; Step S6: soaking the composite material with a mixture of a hydrophobic reagent and an organic solvent to enhance its hydrophobicity and durability, and then performing secondary modification with a cross-linking agent; Step S7: drying the modified composite material under biomimetic normal pressure, using sodium bicarbonate solution as a solvent for drying, using the carbon dioxide generated in the reaction to in-situ support the pore structure to prevent the pore structure from collapsing, and performing molding processing to obtain the final aerogel composite material product.
2. The method for preparing an aerogel composite material according to claim 1, characterized in that: In step S1, the fiber pretreatment, cleaning the glass fiber, removing surface impurities, washing with deionized water, and drying in an oven to constant weight are performed as follows: (1) Immerse the glass fiber completely in deionized water and use ultrasonic cleaning equipment to clean it at a frequency of 30-50kHz for 20-30 minutes to ensure that surface impurities and oil stains are completely removed; (2) After cleaning, use absorbent paper to absorb excess water from the surface of the glass fiber, and then place it in an oven set at 80-100°C to dry for 3-4 hours until it reaches a constant weight.
3. The method for preparing an aerogel composite material according to claim 1, characterized in that: In step S2, methyltrimethoxysilane is selected as the silicon source, the silicon source compound is mixed with the ethanol solvent according to a mass ratio, and the specific steps of using the ethanol sedimentation desalination method to obtain a uniform sol are as follows: (1) Mix the silicon source compound and the ethanol solvent in a mass ratio of 1:5-1:10, and stir them at 300-500 rpm for 30 minutes using a magnetic stirrer at room temperature to ensure uniform mixing; (2) Add salt and stir the mixture to allow ethanol to fully contact with the salt and silicon source compound, accelerate the dissolution and precipitation of the salt, and let the mixture stand for a period of time to allow the ethanol and salt to fully react and other impurities to settle. The salt will gradually dissolve in the ethanol, and other impurities will form solid precipitation; (3) Using a filter or a centrifuge to separate the ethanol gel solution containing the dissolved salt from other impurities that have settled down, until a transparent and uniform sol is formed.
4. The method for preparing an aerogel composite material according to claim 1, characterized in that: In step S3, the pretreated fibers are laid in a mold in a specific direction using an automated fiber laying device, and the aerogel sol is evenly sprayed on the fiber skeleton using a spray device to form a directional composite material structure. The specific steps are as follows: (1) Using automated fiber laying equipment, the pretreated glass fibers are laid in a mold in preset directions of 0°, 45°, and 90° to form a multi-layer directional fiber skeleton; (2) Use a high-pressure spray device to evenly spray the sol onto the fiber skeleton at a pressure of 0.5-1.0 MPa to ensure that the sol fully penetrates and wraps each layer of fiber to form a dense composite material structure.
5. The method for preparing an aerogel composite material according to claim 1, characterized in that: In step S4, the fiber skeleton sprayed with the sol is allowed to stand for natural gelation, and gentle heating may be used to accelerate the gelation process. The specific steps are as follows: (1) The fiber skeleton sprayed with the sol is left to stand at room temperature for 12-24 hours to allow for a natural gelation process; (2) The composite material can be placed in an oven set at 30-50°C for 2-6 hours to accelerate gelation.
6. The method for preparing an aerogel composite material according to claim 1, characterized in that: In step S5, the gel is subjected to solvent replacement using a mixture of water and anhydrous ethanol, and then subjected to aging treatment at a suitable temperature to stabilize the gel structure. The specific steps are as follows: (1) using a mixture of water and anhydrous ethanol in a volume ratio of 1:2-1:5 to perform multiple solvent replacements on the gel, and using a centrifuge or vacuum filtration device to remove residual solvent after each replacement until most of the ethanol is replaced; (2) The replaced composite material is placed in an oven set at a temperature of 60-80°C for aging for 24-48 hours to further stabilize the gel structure.
7. The method for preparing an aerogel composite material according to claim 1, characterized in that: In step S6, the specific steps of soaking the composite material with a mixture of a hydrophobic agent and an organic solvent to enhance its hydrophobicity and durability, and then performing secondary modification with a cross-linking agent are as follows: (1) The composite material is completely immersed in a solution of polydimethylsiloxane and n-hexane in a volume ratio of 1:15 to 1:10 for 6-12 hours to enhance the hydrophobicity of the material; (2) After the immersion is completed, the composite material is taken out and rinsed with n-hexane, and then immersed in a cross-linking agent solution containing glutaraldehyde with a concentration of 0.5%-1.0%. The glutaraldehyde concentration is soaked at room temperature for 1-2 hours for secondary modification to enhance the durability of the material.
8. The method for preparing an aerogel composite material according to claim 1, characterized in that: In step S7, the modified composite material is dried at normal pressure using a sodium bicarbonate solution solvent, the carbon dioxide generated in the reaction is used to support the pore structure in situ to prevent the pore structure from collapsing, and the final aerogel composite material product is obtained by molding. The specific steps are as follows: (1) Sodium bicarbonate solution is evenly coated on the surface of the composite material, and then the composite material is placed in a multi-temperature gradient oven for drying. First, it is dried at 40-60°C for 4-6 hours, then gradually heated to 80-100°C for 6-8 hours, and finally dried at 100-120°C for 2-4 hours. Drawing on the dragonfly eclosion process, the sodium bicarbonate solution generates carbon dioxide gas during the heating process. The gas forms tiny bubbles inside the gel, thereby supporting the pore structure of the gel, making it completely dry and making the pore structure stronger. (2) After drying, cutting, grinding and other molding processes are carried out according to product requirements to finally obtain an aerogel composite material product of the required shape and size.
Citation Information
Patent Citations
A method for preparing an aerogel composite material
CN108911693B
Oriented fiber aerogel heat-insulating compound material and preparation method thereof
CN102503356A
Normal pressure preparation method for silicon dioxide / attapulgite fiber compound aerogel
CN108484098A
Silica aerogel composite material and preparation method thereof
CN118289770A
Methods for preparing aerogels by plasticizing and foaming with solvents
US20220306473A1